2022
DOI: 10.1101/2022.05.06.490973
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amplification is the Primary Mode of Gene-by-Sex Interaction in Complex Human Traits

Abstract: Sexual dimorphism in complex traits is suspected to be in part due to widespread gene-by-sex interactions (GxSex), but empirical evidence has been elusive. Here, we infer the mixture of ways polygenic effects on physiological traits covary between males and females. We find that GxSex is pervasive but acts primarily through systematic sex differences in the magnitude of many genetic effects (″amplification″), rather than in the identity of causal variants. Amplification patterns account for sex differences in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 115 publications
(209 reference statements)
3
20
0
Order By: Relevance
“…First, heritability estimates within strata tend to be higher compared to estimates computed over groups that combine multiple strata (multipopulation, as well as combined sex groups). A similar phenomena was previously reported (74) in a study of sex differences: the authors reported that estimated heritability in sex-combined analysis tended to be lower compared to estimated heritability than that estimated within sex groups, and this pattern became more pronounced when the genetic correlations between male and female genetic effects became lower. Thus, the heritability analysis supports the existence of some differences in OSA genetic architecture between groups.…”
Section: Discussionsupporting
confidence: 80%
“…First, heritability estimates within strata tend to be higher compared to estimates computed over groups that combine multiple strata (multipopulation, as well as combined sex groups). A similar phenomena was previously reported (74) in a study of sex differences: the authors reported that estimated heritability in sex-combined analysis tended to be lower compared to estimated heritability than that estimated within sex groups, and this pattern became more pronounced when the genetic correlations between male and female genetic effects became lower. Thus, the heritability analysis supports the existence of some differences in OSA genetic architecture between groups.…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, genetic correlation analysis between environments has its limitations. A perfect genetic correlation can be achieved when the SNP additive effects are proportional between environments ( Table 1 ; also known as “amplification” in the GxE literature 40 ), leading to false negative results. Even testing both genetic variance and perfect genetic correlation between environments may fail to identify GxE ( Supplementary Note 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other recent studies considered gender differences in genetic determinants of phenotypes, focusing on UK Biobank participants of European ancestries. 48 , 49 Both studies computed genetic correlations between male and female genetic effects for the same phenotype, which we will denote here by to differentiate it from , and found that often this genetic correlation is different than 1, indicating differences in genetic architecture between the gender groups. Zhu et al.…”
Section: Discussionmentioning
confidence: 99%